How do foreign initial public offerings attract investor attention? A study of the impact of language. (August 2019) - Blevins, Dane P; Ingram, Amy; Tsang, Eric WK; Peng, Mike W
Language is increasingly recognized as having the ability to shape strategic outcomes. To understand language's impact in entrepreneurial settings, we study language in the context of foreign initial public offerings, a setting where organizations may suffer from both the liabilities of newness and foreignness. Our sample consists of the population of foreign initial public offerings debuting in the United States between 2001 and 2014, which collectively raised over US60 billion in capital. We find that both new ventures' and the media's language impact investors by influencing the level of interest in the foreign initial public offerings. We also reveal that the media's use of analogies plays a pivotal role in familiarizing and legitimizing unfamiliar organizations. Overall, our study offers insights into the power of words in managing the challenges associated with the liabilities of newness and foreignness.